THE RELEVANCE OF MISYĀR MARRIAGE TO NIGERIAN MUSLIMS - AbdulWahhab Danladi Shittu; Muhammad-Busayri, Sulyman; Ibrahim Mubarak Olalekan (AR-RĀ’IQ, 2023)
Misyār (marriage of convenience) fulfils all the conditions of marriage contract in Islam except that certain conjugal rights are willingly obliterated by the couples. Though, the evolution of misyār in certain civilizations has inextricably invited contentions among Muslim scholars, the relevance of the practice in Nigeria is a thing of concern considering the level of poverty in the country and the fear of its being abused. The study explores scholastic opinions on the lawfulness and benefits of the marriage with a view to assessing its feasibility and relevance within the Nigerian environment using a combination of historical and descriptive research methods. Findings revealed that misyār, though with its advantages, is delicate to practice in Nigeria because it is vulnerably opened to abuse, and it therefore becomes the responsibility of Muslim scholars in the country to rather mature their thoughts and educate the ummah on the circumstances that could necessitate the practice and the limitations to its practicability.